2013 IEEE Applied Electromagnetics Conference (AEMC) 2013
DOI: 10.1109/aemc.2013.7045098
|View full text |Cite
|
Sign up to set email alerts
|

Gain and bandwidth enhancement of a circular microstrip patch antenna with an air dielectric between two substrates

Abstract: This paper describes the circular microstrip antenna with an air gap between two substrates and ground plane using the cavity model theory. The gain and bandwidth improvement is achieved using an air dielectric between two substrates. The microstrip patch antenna was fed by line with an air dielectric between two substrates. The gain of this antenna was 2.39 dB greater and bandwidth was 1.35% greater than that of a conventional circular patch antenna. The method of computation uses MOM and this is enabled by F… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
2
2
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 5 publications
(5 reference statements)
0
3
0
Order By: Relevance
“…The substrates used for simulation are Taconic TLX with a relative permittivity of 3.55, a loss tangent of 0.0019, and a thickness of 0.787 mm. There is an air gap, h between the two substrates, which enhances the impedance bandwidth and improves the radiation efficiency . Through the simulation comparison, it is found that the air gap is helpful to the design of the differential filtering antenna compared with the method of stacking substrate in ref.…”
Section: Antenna Structure and Antenna Mechanismmentioning
confidence: 99%
“…The substrates used for simulation are Taconic TLX with a relative permittivity of 3.55, a loss tangent of 0.0019, and a thickness of 0.787 mm. There is an air gap, h between the two substrates, which enhances the impedance bandwidth and improves the radiation efficiency . Through the simulation comparison, it is found that the air gap is helpful to the design of the differential filtering antenna compared with the method of stacking substrate in ref.…”
Section: Antenna Structure and Antenna Mechanismmentioning
confidence: 99%
“…A gain enhancement of 4.13dBi is achieved using Mushroom like Electromagnetic band gap EBG structure. A circular patch antenna gain and Bandwidth enhancement with air as dielectric substrate [27] is briefed . The MPA is fed gain and hybrid substrate Rogers TMM4 with ferrite ring are explained.…”
mentioning
confidence: 99%
“…A circular patch antenna gain and Bandwidth enhancement with air as dielectric substrate [27] is briefed . The MPA is fed from line between two dielectric substrates by an air.…”
mentioning
confidence: 99%